Acceptance and willingness to pay for DTaP-HBV-IPV-Hib hexavalent vaccine among parents: A cross-sectional survey in China - Aodi Huang; Xia Xu; Lin Tang; Lifang Huang; Jun Li; Xue Zhang; Jiajie Liu; Yang Zhou; Bingling Zhang; Lei Wang; Qian Zhang; Zemei Zhou; et al. (Taylor & Francis Group, 2024)
ABSTRACTDTaP-HBV-IPV-Hib hexavalent vaccine has been used in high-income countries for many years to prevent diphtheria, tetanus, pertussis, hepatitis B, poliomyelitis, and invasive Haemophilus influenzae type b disease. Currently, no hexavalent vaccines have been approved for use in China. Evidence of parental acceptance and interest in hexavalent vaccines can help policy makers and manufacturers make decisions about entering the vaccine market and the immunization program in China. We measured parental acceptance and willingness-to-pay (WTP) for a hexavalent vaccine to provide such evidence. We conducted a cross-sectional survey of children's caregivers in 16 vaccination clinics in seven cities in China and obtained information on socio-demographics, knowledge of disease, confidence in vaccines, previous vaccination experience, and acceptance of and WTP for hexavalent vaccine. Multivariate logistic regression was used to determine factors influencing acceptance, and multivariate tobit regression was used to identify factors impacting WTP. Between April 28 and June 30, 2023, a total of 581 parents of children aged 0-6 years participated in the survey; 435 (74.87%, 95% CI:71.3%−78.4%) parents indicated acceptance of hexavalent vaccine. Residence location, parents' education level, experience paying for vaccination, and disease knowledge scores were key factors affecting parents' choices for vaccination. Mean (SD) and median (IQR) willingness to pay for full 4-dose course vaccination were 2266.66 (1177.1) CNY and 2400 (1600-2800) CNY. Children's age (p < .001), parents' education level (p = .024), and perceived price barriers (p < .001) were significantly associated with WTP. Parents have high acceptance and willingness to pay for hexavalent vaccine. The less money parents have to pay out of pocket, the more willing they can be to accept the vaccine. Therefore, acceptance may increase even further if the vaccine is covered by medical insurance, provided free of charge by the government, or if its price is reduced. Our results provide reference for optimizing and adjusting immunization strategies in China.